Changes in mineral content in trainees' blood and urine due to high-intensity training - Hajdo, Diana; Memić, Mustafa; Domitrović, Robert; Šabanović, Elma (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2019)
High-intensity training is becoming more popular nowadays when people have less time to engage in prolonged physical activity. Expertly led high intensity training is a safe way to achieve desired fitness goals. The aim of the study was to check if there were significant changes in the concentrations of sodium, potassium, calcium, magnesium, zinc, iron and copper in the blood and urine of twelve trainees after a short but intense training. Blood and urine sampling was performed before and after high intensity training where bodyweight exercises and exercises with external load were used. Statistical analysis was performed using paired t-test (2-tailed) with α=0.05 as statistical significance. The results obtained showed that the measured mineral concentrations varied as a result of intense physical activity, but these variations were small and did not have a general trend of increase or decrease of analyzed mineral content. Based on these results, it can be concluded that, from the standpoint of the mineral concentrations loss, short high-intensity training is safe for the trainee’s health.